Effects of dried distiller grains with soluble in replacement of soybean meal in Boer goat diets - Schaake, Shilo S.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
There is very limited data available regarding the role of feeding dried distillers grains with solubles (DDGS) to goats. With the per protein unit cost advantage of DDGS over SBM being $1.86, DDGS would fit into goat diets as a protein source (October 26, 2017 U.S. Grains Council Report). There is insufficient data for goat producers or small ruminant nutritionists to base recommendations for potential inclusion of DDGS in a diet. However, the objective of this experiment was to evaluate the efficiency of DDGS as a replacement for SBM in a growing Boer goat diet. Forty-eight meat goat kids, approximately 70 d of age, were used in a completely randomized design. Animals were housed at the KSU Sheep and Meat Goat Center with 3 kids per pen (4 pens per treatment). Kids were fed one of the four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. All diets were pelleted, with pellets containing roughage, so no supplemental forage was needed. Diets were fed for 47 days, with goats and feeders weighed weekly to determine ADG, ADFI, and G:F. Upon the completion of the project, two random goats from each pen were harvested and carcass data was collected, including: hot carcass weight, carcass yield, loin eye area, loin eye depth, fat thickness, and body wall thickness. The growth and carcass data was evaluated to determine an overall cost/lb. of gain and cost/lb. of product. Data was analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC) with pen serving as the experimental unit. The model will include effects of the level of DDGS with P-value ≤ 0.05 considered significant. Both ADG (P=0.006) and G:F (P= 0.005) increased with DDGS replacing SBM. On the other hand, there was no effect on BW, ADFI, or any carcass data from DDGS. However, the hypothesis stays true that 100% of SBM can be replaced by DDGS without sacrificing growth and performance.
Keywords: Spring 2018